(untitled) (Revista Científica Compendium, 2023)
In an era in which inequalities persist and with a majority of poor countries, it is urgent to expand opportunities for people in conditions of equity, sustainability and deepening of democracy. The education sector plays an important role in advancing towards a fairer world, with development and freedom, so that people can achieve valuable goals. The research was conceived from a socio-constructionist ontoepistemic perspective, starting from the discursive current of the discursive practices method and the in-depth interview technique. It is consubstantiated with the theory of human development and the Agenda 2030. We approach the narratives of six managers of the education sector, their praxis and the way in which from such narratives they build their realities and reflect on the challenges for human development and the Agenda 2030. Among the findings it was found that the instrumental freedoms of social opportunities, protective security and transparency guarantees are very limited. Little progress in the development of capacities and public policies in the sector.